Pengaruh Pelatihan, Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Direktorat Perencanaan Dan Keuangan Pada Rumah Sakit Umum Pusat DR.Wahidin Sudirohusodo Makassar - Suparman, Hendra; Ramlawati, Ramlawati; Asdar Djamereng (Innovative: Journal Of Social Science Research, 2024)
Abstract The Impact of Training, Organizational Culture and Work Environment on the performance of employees at the Directorate of Finance and Planning of Dr. Wahidin Sudirohusodo Makassar General Hospital The variables included in this investigation consist of training (X1), organizational culture (X2), work environment (X3), and employee performance (Y). The study comprised a sample and population of 42 respondents. This study employs quantitative research methodology, specifically utilizing primary data. The process of gathering data was conducted through the utilization of a questionnaire. The sampling methodology employed in this study was the direct appointment method. The analysis methods applied involved tests for data validity, data reliability, normality, multicollinearity, heteroscedasticity, as well as multiple linear regression analysis. Additionally, the study conducted tests for simultaneous influence (F test), partial influence (t test), and simultaneous determination (R2). The findings indicated that: (1) training had a significantly positive influence on the performance of employees at the planning and finance directorate of Dr Wahidin Sudirohusodo Makassar; (2) organizational culture reported a significantly positive effect on the employees at the finance and planning directorate at the Dr Wahidin Sudirohusodo Makassar Central General Hospital; and (3) work environment confirmed a significantly positive impact on the performance of employees at the finance and planning directorate at the Dr Wahidin Sudirohusodo Makassar Central General Hospital. Keywords: Training, Organizational Culture, Work Environment and Employee Performance.